DESIGN OF SAVINGS AND LOAN APPLICATIONS FOR ANDROID-BASED WOMEN'S GROUPS - Fauzi, Fauzi; Nuraini, Sephia; Gunawan, Sahrul (Bakti Nusantara Institute, 2025)
Many savings and loan records in farmer women groups are still done manually using books, which can risk causing errors in recording. This is the background for the development of an offline-based android application that can help the VSLA (Village Saving and Loan Association) savings and loan recording process. The purpose of this research is to build an easy-to-use savings and loan recording application, with a simple appearance and according to the needs of users at the rural community level. Application development is carried out using the kodular platform by utilizing TinyDB local storage so that applications can be used offline. The prototype method used in this study allows the development of the system to be carried out in stages according to user input and requirements. The system is designed using the Unified Modeling Language (UML) approach, which consists of a use case diagram, class diagram, and activity diagram. Group financial management becomes easier and more efficient. With the system created offline-based, the application has proven to be relevant for use in areas that have limited internet connection issues. It is hoped that this research can contribute to efforts to digitize the community financial system, especially for farmer women groups.